PENGGUNAAN MEDIA KARTU KATA BERGAMBAR DALAM PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Novi Yeanti; Zulhendri; Muhammad Syahrul Rizal; Romi Laspita; Melvi Lesmana Alim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to improve students' early reading skills through the use of picture word cards in grade 1 at UPT SDN 024 Limau Manis in the 2024/2025 academic year. The type of research used is classroom action research. The subjects of this study are 15 students, while the objects of this study are picture word cards and improving students' early reading skills. The study was conducted over two cycles, with each cycle consisting of two meetings. The data collection techniques used in this study were observation, testing, and documentation. Based on the increase in the number of students who met the criteria for achieving learning objectives (KKTP) and the improvement in class average scores and classical scores. The classical completion rate in Cycle I Session I was 46.66%, in Cycle I Session II 53.33%, and in Cycle II Session I 66.67%, then in Cycle II Session II 93.34%. Based on the research results, it can be concluded that the use of illustrated word cards can enhance the reading skills of first-grade students at UPT SDN 024 Limau Manis.